Bronchiolitis Simulation Module in the Pediatric Preclerkship Educational Exercises (PRECEDE) Curriculum - Justin M. Jeffers; Amit Pahwa; Stacy Cooper; Olivia Widger; David W. Cooke; Emily Frosch; Rebekah Reisig; Christopher Grybauskas; Eric Balighian; Lauren Kahl; Edward L. Bartlett; W. Christopher Golden (Association of American Medical Colleges, 2023)
Introduction Acute bronchiolitis is a viral infection infecting 90% of children under the age of 2 years, with approximately 200,000 deaths per year. The current standard of care remains largely respiratory support and prevention. Therefore, understanding how to assess and escalate respiratory supportive care is paramount for health care providers taking care of children. Methods We used a high-fidelity simulator to simulate an infant with progressing respiratory distress in the setting of acute bronchiolitis. The participants were pediatric clerkship medical students during their preclerkship educational exercises (PRECEDE). The students were asked to evaluate and treat the simulated patient. After debriefing, the students repeated the simulation. We assessed both performances via a weighted checklist specifically developed for this case to measure team performance. Students also completed an overall course evaluation. Results Ninety out of 121 pediatric clerkship students were enrolled. Performance improved from 57% to 86% ( p < .05). Donning appropriate personal protection equipment was the most missed item both pre- and postdebriefing. Overall, the course was well liked and received. Participants requested more simulation opportunities within PRECEDE as well as a summary document to reinforce learning. Discussion Pediatric clerkship students improved their performance managing progressing respiratory distress due to acute bronchiolitis via a performance-based assessment tool with sound validity evidence. Improvements going forward include improving faculty diversity and offering more simulation opportunities.